THE EFFECT OF THE USE OF ARTIFICIAL INTELLIGENCE, PERSONALIZED MARKETING, AND CUSTOMER EXPERIENCE ON CUSTOMER LOYALTY (Case Study on the Spotify Digital Music Platform) - Ulya Alfandi; Jullimursyida; Mariyudi; Adnan (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Artificial Intelligence (AI), Personalized Marketing, and Customer Experience on Consumer Loyalty on the Spotify digital music platform. The research was conducted at Universitas Malikussaleh, located in Bukit Indah, Muara Dua Sub-district, Lhokseumawe City, Aceh. The population in this study consists of active students of Universitas Malikussaleh who use Spotify, with a purposive sampling technique and a total sample of 120 respondents. Data collection was carried out through surveys using both offline and online questionnaires. The data analysis method used was Multiple Linear Regression, which included tests for validity, reliability, classical assumptions, t-tests, F-tests, and coefficient of determination (R²). The results show that simultaneously, the three independent variables have a significant effect on consumer loyalty. Partially, Artificial Intelligence has the greatest and most significant influence (β = 0.444; sig = 0.000). Customer Experience also has a significant effect (β = 0.251; sig = 0.001), while Personalized Marketing does not show a significant effect (β = 0.176; sig = 0.109). These findings indicate that Artificial Intelligence technology and good user experience play an important role in retaining Spotify users. This research is expected to serve as a reference for developing digital marketing strategies in the music streaming industry, particularly within the freemium business model like Spotify.